"A slumber did my spirit seal": Wrestling with Paul Fry on His Own Wordsworthian Terrain. Issue 1 (1st April 2023) - Weinfield, Henry
Abstract : This essay focuses on Fry's theory of poetry, especially as he develops it in A Defense of Poetry: Reflections on the Occasion of Writing (1995) and Wordsworth and the Poetry of What We Are (2008), by examining his various discussions of Wordsworth's lyric, "A slumber did my spirit seal." For Wordsworth in the "Preface to Lyrical Ballads, " meter, rather than being imbricated with meaning, is "superadded, " and for the anti-formalist Fry what distinguishes poetry from other forms of discourse is not verse but rather its relation to what he calls "insignificance." In examining "A slumber" against Fry's discussions of the poem, I argue both that its meaning cannot be separated from its meter, as Fry's analysis itself paradoxically reveals (in other words, that Wordsworth's practice is at variance from his theory), and that the poem's meter reveals an intertextual connection that allows it to be read as having a significant moral message. Against the postmodern perspective that Fry delineates in A Defense, I conclude (somewhat quixotically) by arguing that poetry needs to be defined and defended in terms of verse.